Omni-Channel Trends in Covid-19 Pandemic - Avşar, Beyza Zeynep; Istanbul Commerce University (Journal of International Trade, Logistics and Law, 2021)
Beginning with the realization of an exigency and finishing with a post-journey review, a customer's experience is divided into many stages. This experience is largely defined by consumers shifting between platforms (e.g., store, retailer website, price comparison app) across and inside platforms in today's omni-channel context. It is even typical for them to utilize many platforms at the same time (e.g., checking online prices inside a real-world store). The evolving characteristics of the consumer experience has become a prominent theme in marketing research Especially, the COVID-19 pandemic has escalated to changes from retailer's sides. During this period, retailers went for changes to provide the best services for the customers to survive. The aim of this article to find out the latest omni-channel trends to how retailers adopting themselves in this new era.